2011
DOI: 10.1097/crd.0b013e318214022b
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary In-Hospital Management Strategies for Acute Decompensated Heart Failure

Abstract: Acute decompensated heart failure (ADHF) is a common syndrome with diverse etiologies and precipitating factors, which is associated with significant morbidity and mortality. Tremendous resources are used in treating this syndrome, with few prospectively designed clinical trials to guide therapy. Patients suffering from ADHF are at increased risk for readmission to the hospital as well as an increased risk of death. Prompt identification and management of these patients can lead to shorter length of hospital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
1
0
0
Order By: Relevance
“…Furthermore, at 3 months the total mortality rate was found to be 14.2%, which is in agreement with findings from a recently reported large cohort study, which found a short‐term mortality of 18% after VKA‐related hospitalization . Consequently, the mortality after hospitalization for VKA‐related bleeding is higher than the reported mortality of patients of an equal age hospitalized for other (non‐malignant) reasons such as decompensated heart failure or severe community‐acquired pneumonia .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, at 3 months the total mortality rate was found to be 14.2%, which is in agreement with findings from a recently reported large cohort study, which found a short‐term mortality of 18% after VKA‐related hospitalization . Consequently, the mortality after hospitalization for VKA‐related bleeding is higher than the reported mortality of patients of an equal age hospitalized for other (non‐malignant) reasons such as decompensated heart failure or severe community‐acquired pneumonia .…”
Section: Discussionsupporting
confidence: 90%